The application of Islamic Law relating to non-consensual sexual offence: a comparative study - Mohamad Yunus, Mohamad Ismail (Institut Kefahaman Islam Malaysia (IKIM), 2002)
Islam is religion and way of life based on the commandments of Allah (God) contained in the Holy Quran and Sunnah of the Prophet Muhammad (peace be upon him). Every believer is under an obligation to fashion his or her entire life in accordance with teachings of Quran and Sunnah. Therefore, the believers have to observe at every step the distinction between what is lawful (halal) and what is unlawful (haram). This highlights the need and importance of acquaintance with the Islamic law (Shariah). Generally speaking, in modern secular system consensual sexual relationship outside marriage are not considered a crime. Such sexual freedom is completely unknown to all the sacred laws. The Jewish, the Christian, and the Islamic laws all forbid, and rather render punishable, all types of sexual relationship outside marriage. The differences between these laws appear in what are considered unlawful and punishable sexual relations, and the punishments prescribed for the prohibited practices. The incidence of sex crimes in the form of indecent assault, rape, sodomy, bestiality adultery, fornication and incest has become too common nowadays. The complexities have enormously increased with the advance of science, civilization and culture. Modern urbanization has brought total disintegration of the society which has led to these serious problems in human life. This article is aimed at studying and examining the past and present law relating to sexual offences under the Islamic law and to compare with the laws at the common law jurisdiction such as in England, Canada, Australia, New Zealand, including Malaysia. Besides, it is the objective of this article to consider the proposals and reforms on those laws based on the fundamental principle of protecting the integrity of the nations and individuals. Lastly, it is also interesting to note that it is important to study the article in order to identify whether the main aim of formulating the law relating to sexual crimes (i.e. to protect especially, the female, young persons, minors and mentally retarded against non-consensual sexual intercourse) is achieved or not at some extent of its implementation. I am confident that the Muslim and non-Muslim legal researchers, legal practitioners, members of the judiciary, law lecturers, policemen and lay men will find this article valuable and useful as it contains a comprehensive analysis of the law relating to sexual offences with special reference to the law of rape.